Family history, body mass index and survival in Japanese patients with stomach cancer: a prospective study. Issue 2 (17th June 2014) - Minami, Yuko; Kawai, Masaaki; Fujiya, Tsuneaki; Suzuki, Masaki; Noguchi, Tetsuya; Yamanami, Hideaki; Kakugawa, Yoichiro; Nishino, Yoshikazu
<x xml:space="preserve">Abstract</x> Family history and nutritional status may affect the long‐term prognosis of stomach cancer, but evidence is insufficient and inconsistent. To clarify the prognostic factors of stomach cancer, we conducted a prospective study of 1, 033 Japanese patients with histologically confirmed stomach cancer who were admitted to a single hospital between 1997 and 2005. Family history of stomach cancer and pretreatment body mass index (BMI) were assessed using a self‐administered questionnaire. Clinical data were retrieved from a hospital‐based cancer registry. All patients were completely followed up until December, 2008. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated according to family history in parents and siblings and BMI category. During a median follow‐up of 5.3 years, 403 all‐cause and 279 stomach cancer deaths were documented. Although no association with family history was observed in the patients overall, analysis according to age group found an increased risk of all‐cause death associated with a history in first degree relatives (HR = 1.61, 95% CI: 0.93–2.78, p = 0.09) and with a parental history (HR = 1.86, 95% CI: 1.06–3.26) among patients aged under 60 years at diagnosis. BMI was related to all‐cause and stomach cancer death among patients aged 60 and over, showing a J‐shaped pattern (HR of all‐cause death = 2.28 for BMI < 18.5; HR = 1.61 for 25 ≤ vs. ≥ 23.0 to < 25.0 kg/m2). A family history of stomach cancer, especially parental history, may affect mortality among younger stomach cancer patients, whereas nutritional status may be a prognostic factor in older patients.